The effect of product market competition on job instability - Ainhoa Aparicio Fenoll (Institute for the Study of Labor (IZA), 2011)
This paper assesses the impact of product market competition on job instability as proxied by the use of fixed-term labor contracts. Using both worker data from the Spanish Labor Force Survey and firm data from the Spanish Business Strategies Survey, I show that job instability rises with competition. In particular, a one standard deviation increase in competition in an economic sector decreases the probability that a fixed-term worker gets an open-ended contract within that sector in a given year by more than 30%. The effect is identified by means of exogenous shifts in competition brought about by changes in legislation.
urn:nbn:de:101:1-201105173047
Keywords: J24; M51; C41; C33; C35; J6; L1; 330; product market competition; fixed-term employment; labor contract; Arbeitsplatzsicherung; Wettbewerb; Arbeitsverhältnis; Schätzung; Spanien